Resposta :
Olá,
[tex] \tt \: (b + y) + (x + a) \\ [/tex]
Podemos manipular a soma acima:
[tex] \tt \: (b + y) + (x + a) \\ = \tt \: b + y + x + a \\ \tt \: = x + y + a + b \\ \tt \: = (x + y) + (a + b) \\ [/tex]
Substituindo os valores dados:
[tex] \tt \: (b + y) + (x + a) \\ \tt \: = (x + y) + (a + b) \\ \tt \: = (8) + (6) \\ \tt \: = 14[/tex]
HEY BRO
Basta substituir os parênteses:
[tex]\tt(b + y) + (x + a) = \\ \tt b + y + x + a = \\ \tt (x + y) + (a + b) = \\ \boxed{\tt 8 + 6 = 14}[/tex]
[tex]\boxed {\tt BURNS}[/tex]